The Problems and Intentions of Structuralist Theory: The Mathematics of Mahur Beste - aydin satar, nesrin (Journal of History Culture and Art Research, 2015)
The Problems and Intentions of Structuralist Theory: The Mathematics of Mahur Beste Abstract Berna Moran points out that structuralism is not only a literary theory but also a method which can be applied to various disciplines like anthropology, psychology and sociology. (Moran, 2008, p.185) Actually, this theory has gained importance with the publication of notes of the lecture by Ferdinand de Saussure and their effects on radical changes in the field of linguistics. On the other hand, because the theory aims to search out deep structure of the elements of communication that we experience any time in everyday life, the application of this theory in social sciences is not surprising. It is possible to think that using structuralist theory in literary texts means to ignore the literary side of the text. It is because, the literary text is usually written with feelings, not mathematical reasoning. On the other hand, it might be described as a problem that structuralist theory focuses on only a text, and it neglects the writer and the social, cultural or economic conditions that create a text. Nevertheless, the structuralist theory offers many data about deep/basic structure of the text. This paper examines the troubles and utility of structuralism leaded by linguists and literature theorists such as Ferdinand de Saussure, Viktor Shklovsky and Roman Jakobson. After this examination, Ahmet Hamdi Tanpınar’s novel, Mahur Beste is analyzed with the theory and the mathematical side of novel is found out. By this way, it is shown how the structuralism is used to reach the deep structure of literary text.